Do delays in radiology lead to breaches in the 4-hour rule?. Issue 6 (June 2016) - Tse, R.; Thompson, N.; Moscova, M.; Sindhusake, D.; Shetty, A.; Young, N.
Abstract : Aim: To assess trends in medical imaging requests before and after the 4-hour rule commenced and to assess the imaging time component of emergency department (ED) length of stay (LOS). Materials and methods: Retrospective analysis of ED patients and imaging requests 1 year prior to and 3 years after implementation of the 4-hour rule (April to December for 2011–2014) was performed at a single adult tertiary referral Level 1 trauma hospital with Level 6 ED. Logistic regression was used to evaluate trends in the number of ED patient presentations, patient triage categories, and imaging requests for these patients. The imaging component of the total ED LOS was compared for patients who met the 4-hour target and patients who did not. Results: Compared to 2011 (before the 4-hour rule), ED presentations increased 4.74% in 2012, 12.7% in 2013, 21.28% in 2014 ( p <0.01). Total imaging requests increased 23.05% in 2012, 48.04% in 2013, 60.77% in 2014 ( p <0.01). For patients breaching the 4-hour rule, the mean time before radiology request was 2.4–2.8 hours; mean time from imaging request to completion was 1.2–1.3 hours; mean time from imaging completion to discharge from ED was the longest component of ED LOS (4.9–5.9 hours). Conclusions: There has been a significant increase in imaging requests, with a trend towards more CT and less radiography requests. Imaging requests for patients who breached the 4-hour target were made on average 2.4–2.8 hours after triage and average time after imaging in itself, exceeded 4 hours. Imaging is not likely a causative factor for patients breaching the 4-hour target. Highlights: Since the introduction of 4-hour rule we report an increase of up to 60.77% in the total number of imaging requests. A shift towards using greater proportion of CTs and smaller proportion of X-rays was observed. Imaging was unlikely to be a causative factor in the 4-hour target breaches, as average time after imaging exceeded 4 hours.